(untitled) (Bangladesh Journal of Medical Education, 2017)
Background: For the first 20 years or so after formal education in dentistry commenced at Glasgow in 1879, the manner of learning technical and clinical procedures was little different from what it had been since immemorial. In other words dental students learned by watching others until it was felt that they could be trusted to perform the procedure themselves. Rationale: The intern year is the first level of hands-on training in dentistry and is an essential step in every dental surgeon’s career. Opportunity to apply, consolidate and expand one’s clinical knowledge, skills and also progressively increase one’s responsibility for providing safe, high-quality patient care. Opportunity to develop overall patient management skill especially for the general dental practitioner. The intern year should provide a balance between education, training and clinical responsibility, enabling interns to develop the professional and personal competencies that result in good patient care and provide a foundation for lifelong learning. Objectives: The present study was undertaken to identify the Competency based internship training programme in undergraduate dental education in Bangladesh: Clinical teachers and intern doctors’ perception Methods: This descriptive type of cross sectional study was conducted in six public and private dental colleges of Bangladesh. A semi-structured questionnaire based on 5-point Likert scale was used to collect the clinical teachers and inter doctors’ perceptions. The semi-structured questionnaire was prepared on the basis of logbook based internship training programme. Before administering the questionnaires to the respondents the investigator gave them an introductory idea about the purpose of the research. Results: competencies acquired by the intern doctors were satisfactory but some problematic areas such as less duration of training period, no community placement, availability of training aid, lack of supervision as well as feedback etc were highlighted which interfered in achieving their satisfaction on their competencies. Conclusion: To ensure excellence in all aspects of internship training programme, it can be concluded that intern doctors must need to acquire sufficient competencies in most of the clinical areas for their daily practice. There are many areas for further improvement through evaluating and developing the internship training programme as well as the logbook and strengthening the clinical environment in the institutes. Bangladesh Journal of Medical Education Vol.8(1) 2017: 9-13